Examining the impact of financial ratios on stock prices of large banks listed on the Indonesia stock exchange - Gunawan, Riki; Hasanah, Lak lak Nazhat El (Nur Science Institute, 2024)
This research aims to determine the effect of financial ratios on the stock prices of big banks listed on the Indonesia Stock Exchange in 2013-2022. The financial ratios used in this study are Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Return on Equity (ROE), Operating Costs Operating Income (BOPO), and Bank Indonesia interest rates (BI). The population in this study were banking companies listed on the Indonesia Stock Exchange during 2013-2022. The research sample was 12 banking companies obtained using purposive sampling techniques. The data collected were taken from the OJK, BPS, and BEI websites. The method in this study uses quantitative data analysis. The results of the study show that simultaneously the variables CAR, NIM, ROE, BOPO, and Bank Indonesia interest rates affect stock prices. Partially, the variables NIM, ROE, BOPO, and Bank Indonesia interest rates have a negative effect on stock prices, while the CAR variable does not affect stock prices.